Pada Mulanya Ayah, Lalu Buya, Kemudian Iqbal, Akhirnya W.s. Rendra - Alka, David Krisna (MAARIF Institute, 2023)
In particular, there has been no particular study that thoroughly explores the traces of Ahmad Syafii Maarif’s (Buya Syafii) thought in the cultural realm. As the title of this journal suggests, it seems like an attempt to look at Buya Syafii’s cultural road map. However, in fact, all of Buya’s thoughts and ways of life were culture itself, humans and humanity in their manners and civilisation. This paper presents the author’s intention to trace the path of Buya’s association with culturalists, his views and admiration for their works, thoughts and cultural movements. It starts with Buya’s association with Pakistani poets, Muhammad Iqbal, and Rendra.